Carcinogenicity and hormone studies with the tissue‐selective estrogen receptor modulator bazadoxifene1. Issue 4 (20th December 2012) - Wright, David J.; Earnhardt, J. Nicole; Perry, Richard; Bailey, Steven; Komm, Barry; Minck, Daniel R.; Cukierski, Mark A.
Abstract Bazedoxifene Acetate (BZA) is a selective estrogen receptor modulator (SERM) that is approved for the prevention and/or treatment of osteoporosis in postmenopausal women. To assess for carcinogenic potential, BZA was administered ad libitum in the diet to rats for 2 years. BZA caused an increase in benign ovarian tumors in female rats and decreased incidences of mammary tumors (females) and pituitary tumors (males and females). In addition, BZA provided a significant survival benefit at all dosages tested, which correlated with a significant reduction in pituitary and mammary gland tumors and decreased body weight gain (both genders). Additional studies were subsequently conducted in rats and monkeys to further explore the mechanisms likely responsible for the observed effects. Results from studies in hypophysectomized and chemically castrated female rats indicated that BZA did not directly stimulate formation of ovarian cysts, but an intact pituitary was required for cyst formation. Further, BZA increased estradiol concentrations in rats and monkeys. In monkeys, BZA increased concentrations of luteinizing hormone (LH) after onset of treatment and prohibited the preovulatory surge of LH until after cessation of treatment. These hormonal changes suggest that BZA inhibited both the positive and negative feedback effects of estrogen on gonadotropins and the resulting increase in LH caused formation and persistence of ovarian cysts, which eventually transformed into benign ovarian granulosa cell tumors in the rat carcinogenicity study. These results also suggest that the reductions in pituitary and mammary gland tumors were attributed to BZA‐related antagonism of endogenous estrogens at the estrogen receptors. J. Cell. Physiol. 228: 724–733, 2013. © 2012 Wiley Periodicals, Inc.